2004
DOI: 10.1254/jphs.fpj04008x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Release From Oridonin-Treated Apoptotic A375-S2 Cells Is Dependent on p53 and Extracellular Signal-Regulated Kinase Activation

Abstract: Abstract. We have reported that oridonin isolated from Rabdosia rubescens induces apoptosis of human melanoma A375-S2 cells within 12 h. In this study, TUNEL assay and flow cytometric analysis also indicate that one of the causes of A375-S2 cell death induced by oridonin was apoptosis. The cell death was preceded by the release of cytochrome c from the mitochondria. Twelve hours after treatment with oridonin, the ratio of Bax / Bcl-xL protein expression was increased and release of cytochrome c was decreased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 32 publications
(35 reference statements)
1
34
0
Order By: Relevance
“…[4][5][6][7][8] Inhibition of PI3K, PKC, MAPK, NFkB and activation of p53 have been suggested to underlie the effects of oridonin. [5][6][7][8][9]22,23 Our results in this study demonstrated that oridonin decreased cell viability in all the 3 tested cell lines in concentration-and time-dependent manner. The predominant mode of cell death in these cells was apoptosis, as determined by characteristic changes in cell morphology with Hochest 33258 staining and by the presence of sub-G 1 peak with flow cytometry measurement.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[4][5][6][7][8] Inhibition of PI3K, PKC, MAPK, NFkB and activation of p53 have been suggested to underlie the effects of oridonin. [5][6][7][8][9]22,23 Our results in this study demonstrated that oridonin decreased cell viability in all the 3 tested cell lines in concentration-and time-dependent manner. The predominant mode of cell death in these cells was apoptosis, as determined by characteristic changes in cell morphology with Hochest 33258 staining and by the presence of sub-G 1 peak with flow cytometry measurement.…”
Section: Discussionsupporting
confidence: 55%
“…46 There are very limited studies on the regulation and function of MAPKs in oridonin-induced cell death. Oridonin has been demonstrated to induce the activation of ERK1/2 and inactivation of p38 MAPK in human macrophage-like U937 cells, murine fibrosarcoma cell line L929 and A375-S2 cell line 9,22,47,48 whereas, the activities of JNK was not affected by oridonin. 47 Inconsistent with these reports, our study demonstrated that oridonin treatment induced marked inactivation of ERK and activation of p38 MAPK and JNK.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have demonstrated that oridonin exerted inhibitory effects on various cancers such as human prostate carcinoma, non-small cell lung cancer, acute promyelocytic leukemia, and glioblastoma multiforme (5). In our previous study, we found that oridonin induced A375-S2 cell apoptosis via the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) pathway (6). In addition, we have shown that oridonin enhances 12-O-tetradecanoylphorbol-13-acetate (TPA)-treated U937 cells to phagocytose UVirradiated apoptotic U937 cells by a mechanism involving tumor necrosis factor (TNF) α and interleukin (IL)-1β release (7).…”
Section: Introductionmentioning
confidence: 93%
“…In the aggressive HT1080 fibrosarcoma cell line, oridonin has been shown to induce apoptosis through a p53-mediated mechanism that is regulated by nF-κB (20). another study with the human melanoma a375-S2 cell line also demonstrated that oridonin acts via a p53-mediated mechanism inhibited by blocking pi3-K pathway activation (21).…”
Section: Discussionmentioning
confidence: 98%